Safety effectiveness of forward collision warning systems in the vehicle fleet: A driving simulation study - Olufowobi, Oluwaseun; Ivan, John; Wang, Kai; Eluru, Naveen (Accident analysis and prevention, 2025)
•A driving simulation study evaluated how effectively Forward Collision Warning (FCW) systems help prevent conflicts.•Swedish Traffic Conflict Technique used to estimate Crash Modification Factors for vehicles with FCW systems.•Chi-square tests were used to validate serious conflict reductions and support the calculation of CMFs.•FCW systems reduced serious conflicts and crash risk, notably in urban areas and scenarios involving pedestrians. The increasing rate of crashes globally has prompted the development of strategies like the Advanced Driver Assistance systems (ADAS) to improve safety. These systems range from subtle speed adjustment alerts to automatic emergency braking. One such system is the forward collision warning (FCW), which aims to mitigate collisions, particularly rear-end crashes, by providing visual, auditory, or tactile alerts of impending collisions. However, there has not been enough attention given to how drivers might react to FCW without unintentionally distracting them, while also using serious conflicts to quantify safety. This driving simulation study aimed to assess the effectiveness of the FCW by examining serious conflict as a surrogate measure for actual crashes. The goal was to estimate a Crash Modification Factor (CMF) for FCW systems within vehicle fleet, considering varying market penetration rates ranging from 10 percent to 50 percent in increments of 10 percent. Scenarios were created where drivers encountered different road and traffic conditions to evaluate their responses to unexpected events. A total of 133 participants completed a between subject design in which half of them drove the course with the FCW programmed into the simulation, and the other half did not have the FCW. The evaluation of serious conflicts utilized the Swedish Traffic Conflict Technique, employing two key indicators: Time to Accident (TA) and Conflicting Speed. Conflict severity was measured by considering two variables − the lane position and speed of the participants which was used to compute the TA. As expected, drivers in each scenario experienced fewer serious conflicts when assisted by FCW systems compared to the drivers without them. The resulting CMFs from the study can be integrated into crash prediction models to support efforts to keep crash prediction models up to date by accounting for the effects of increasing numbers of vehicles having FCW systems.